The THE IMPACT OF SINGAPORE COASTAL RECLAMATION AGAINST MARITIME BOUNDARIES AND TERRITORIAL SOVEREIGNTY OF INDONESIA-SINGAPORE - Hardi Alunaza; Arni Nur Sukma Pertiwi; Adityo Darmawan Sudagung (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2018)
Singapore has undertaken coastal reclamation activities since 1976 in the southwest of Singapore's main island bordering the Nipa Island, Riau Archipelago, Indonesia. In reclamation, Singapore took sand from Nipa Island Indonesia bounded by the sea with Singapore. This reclamation will have an impact on several things that is the maritime boundaries and the territorial sovereignty of both countries. This article is attempted to describe how the impact of Singapore coastal reclamation against the maritime boundary and territorial sovereignty of Indonesia-Singapore. The author is using the concept of State Sovereigntynd the International Maritime Law in UNCLOS 1982. Furthermore, this paper is using the descriptive method with the qualitative approach. The data collection technique is literature study consisting of books, journals, and including data from the reliable website in supporting the explanation of this paper. Based on the provisions of UNCLOS 1982, it can be concluded that Singapore's coastal reclamation has no effect on the maritime boundary between Indonesia and Singapore, where maritime boundaries remain at baseline before Singapore reclamates. However, Singapore's coastal reclamation could threaten Indonesia's territorial sovereignty as the mainland of Singapore approaching Nipa Island Indonesia can assume that Singapore wants to take control of Nipa Island, especially the Nipa Island region is strategically located because of its near to the Singapore Strait which is an international shipping line. Abstrak Singapura telah melakukan kegiatan reklamasi pantai sejak 1976 di barat daya pulau utama Singapura yang berbatasan dengan Pulau Nipa, Kepulauan Riau, Indonesia. Dalam reklamasi, Singapura mengambil pasir dari Pulau Nipa Indonesia yang dibatasi langsung oleh laut dengan Singapura. Reklamasi ini akan berdampak pada beberapa hal, yaitu batas maritim dan kedaulatan teritorial kedua negara. Tulisan ini memaparkan bagaimana dampak reklamasi pantai Singapura terhadap batas maritim dan kedaulatan teritorial Indonesia-Singapura. Dalam tulisan ini, penulis menggunakan konsep Kedaulatan Negara dan Hukum Laut Internasional UNCLOS 1982. Dengan menggunakan metode deskriptif dan pendekatan kualitatif, data yang disajikan dalam artikel ini bersumber dari studi pustaka, baik buku, jurnal, serta data dari website guna mendukung penjelasan akhir. Berdasarkan ketentuan UNCLOS 1982, dapat disimpulkan bahwa reklamasi pantai Singapura tidak berpengaruh pada batas maritim antara Indonesia dan Singapura, di mana batas-batas maritim tetap pada kesepakatan awal sebelum Singapura melakukan reklamasi. Namun, reklamasi pantai Singapura dapat mengancam kedaulatan teritorial Indonesia karena daratan Singapura yang mendekati Pulau Nipa Indonesia dapat diasumsikan bahwa Singapura ingin menguasai Pulau Nipa, terutama wilayah Pulau Nipa yang strategis karena letaknya yang dekat dengan Selat Singapura yang merupakan jalur pelayaran internasional. Kata kunci:Batas Maritim; Kedaulatan Teritorial; Reklamasi Pantai